EXPLORING STUDENTS' PERCEPTION OF QUESTIONING STRATEGIES USED BY ENGLISH TEACHERS IN THE CLASSROOM AT SMPN 27 MAKASSAR - Khatimah, Husnul; Korompot, Chairil Anwar; Aeni, Nur (Universitas Negeri Makassar, 2025)
This study focuses on students' perceptions of the questioning strategies employed by English teachers at SMPN 27 Makassar. Using qualitative methods, including observation and interviews with 20 students from two different classes, the research examines how students' perceptions influence their understanding, classroom engagement, and critical thinking. The findings indicate that most students hold a positive perception of the questioning strategies used by their teachers. They believe that these strategies help enhance their understanding of the material, foster deeper thinking, and encourage active participation in discussions. Students appreciate questions that require in-depth explanations and those that challenge them to connect new concepts with previously learned material. Many students also noted that the relevance of questions to the lesson content contributed to a more structured and focused learning experience. However, some students expressed the need for more time to think before answering more complex questions, highlighting the importance of pacing in effective questioning techniques. Despite occasional nervousness, students generally found the questioning process motivating, as it increased their confidence in responding and engaging with the class. The variety of questioning strategies used also created an inclusive learning environment, allowing students to feel comfortable and encouraged. Overall, students' positive perceptions underscore the importance of well-implemented questioning strategies in promoting a more interactive and productive learning environment.